Thrombotic and hemorrhagic complications during visceral transplantation: risk factors, and association with intraoperative disseminated intravascular coagulation‐like thromboelastographic qualities: a single‐center retrospective study. (5th June 2018) - Raveh, Yehuda; Rodriguez, Yiliam; Pretto, Ernesto; Souki, Fouad; Shatz, Vadim; Ashrafi, Behrouz; Manmohansigh, Vinaya; Demos, Michael; Livingstone, Joshua; Nasrallah, Georges; Andrews, David; Beduschi, Thiago; et al.
Summary: This study describes the risk of thrombotic and hemorrhagic complications, both intraoperatively, and up to 1 month following visceral transplantation. Data from 48 adult visceral transplants performed between 2010 and 2017 were retrospectively studied [32 multivisceral (MVTx); 10 isolated intestine; six modified‐MVTx]. Intraoperatively, intracardiac thrombosis (ICT)/pulmonary embolism (PE) occurred in 25%, 0% and 0% of MVTx, isolated intestine and modified MVTx, respectively, and was associated with 50% (4/8) mortality. Preoperative portal vein thrombosis (PVT) was a significant risk factor for ICT/PE ( P = 0.0073). Thromboelastography resembling disseminated intravascular coagulation (DIC) (r time <4 mm combined with fibrinolysis or flat‐line) was statistically associated with occurrence of ICT/PE ( P < 0.0001). Compared to subgroup without ICT/PE, occurrence of ICT/PE was associated with an increased demand for all blood product components both overall, and each surgical stage. Hyperfibrinolysis (56%) was identified as cause of bleeding in MVTx. Incidence of postoperative thrombotic event at 1 month was 25%, 30% and 17% for MVTx, isolated intestine and modified MVTx, respectively. Incidence of postoperative bleeding complications at 1 month was 11%, 20% and 17% for MVTx, isolated intestine and modified MVTx. In conclusion, MVTx recipients with preoperative PVT are at an increased risk of developing intraoperative life‐threatening ICT/PE events associated with DIC‐like coagulopathy.